Pharmacokinetics, safety, efficacy and immunogenicity of Adalimumab biosimilar ABP-501in rheumatoid arthritis and plaque psoriasis - Akter, Anika (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.